BIMBINGAN BAGI MASYARAKAT DALAM PROSES PENGISIAN DATA E-KTP PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (DUKCAPIL) KOTA PALANGKA RAYA - ani, Sam'; Rosiani, Rosiani; Putra, Rasyid Novta Pramadhana; Putra, Kristianarco Utama; Siska, Siska Pratama; Ichsan, Mochammad; Haris, Ferdiyani (Jurnal Abdimas Gorontalo (JAG), 2023)
Community service activities which are one form of student obligation at the Palangkaraya School of Informatics & Computer Management (STMIK) include completing Integrated Field Work Practices (PKL) before graduating which aims not only to direct students to practice the knowledge they have gained during college but also adopting community service activities, which in this activity take the form of guidance in making E-KTPs for the people of Palangka Raya city at the Department of Population and Civil Registration (DUKCAPIL) of Palangka Raya city. Filling in E-KTP data is a crucial stage in efforts to accurately identify residents. The Department of Population and Civil Registration (Dukcapil) of Palangka Raya City has identified challenges in filling in data faced by the community, resulting in incomplete identity documents. This guidance helps the public understand the process of filling in E-KTP data better, reduces errors in filling in data, and speeds up the process of applying for E-KTP. Apart from that, this guidance program also increases public awareness of the importance of having an E-KTP as an official identity. This PKL activity in the form of community service will be carried out from July 10 to September 1 2023. The target of this community service activity is people who will make E-KTPs in the city of Palangka Raya. The method of this activity is in the form of direct service using the application system available at the Palangka Raya city DUKCAPIL service. The result of this community service is that the people of Palangka Raya city who will make E-KTP are well served